A cross-sectional, clinical study to evaluate mobility of teeth during pregnancy using periotest - Poonam Sujeet Mishra; Pramod P Marawar; Sunil Surendraprasad Mishra (Wolters Kluwer Medknow Publications, 2017)
Background and Objective: Over a century, an increased prevalence of gingival diseases associated with increasing plasma sex steroid hormone levels has been reported. These situations present unique challenges to the oral health-care professional. It is believed that hormonal fluctuations such as those associated with pregnancy, menstruation, and use of hormonal contraceptives lead to an increase in tooth mobility. However, this effect of female sex hormones on periodontal ligament and tooth-supporting alveolar bone has rarely been investigated. Hence, this study was conducted to understand the effect of hormonal changes during pregnancy on tooth mobility. Materials and Methods: Mobility of index teeth 16, 13, 21, 23, 24, 36, 33, 41, 43, and 44 was measured with periotest for fifty pregnant females at first trimester (12th week), second trimester (24th week), and third trimester (35th week). Simplified oral hygiene index, plaque index, Gingival index (GI), and probing depth were also evaluated during the three trimesters of pregnancy for each subject participating in the study. Statistical Analysis: The results of the study were subjected to statistical analysis. Data analysis was done by applying Z-test for comparing difference between two sample means. Results: A small but statistically significant influence on the periotest value was seen during the three trimesters of pregnancy. GI scores significantly increased throughout pregnancy despite no significant change in plaque levels. Conclusion: Pregnancy had a significant influence on tooth mobility. Highest value of tooth mobility was seen in the last month of pregnancy. The maximum severity of gingivitis was also seen during the third trimester of pregnancy.